Perubahan Level Ansietas Dengan Penerapan Metode Kangaroo Mother Care (KMC) Pada Ibu Postpartum - Syenshie Wetik; Ferlan Pondaag; Feronica Imbing (Jurnal Kesehatan, 2025)
Anxiety is a common problem experienced by many individuals, including postpartum mothers. The causes include worry about the baby's condition, feelings of inadequacy in caring for the baby, unpreparedness to care for the baby and family, and various other reasons. This condition can negatively affect the mother, baby, and family as caregivers. One alternative to reduce anxiety in postpartum mothers is the implementation of the Kangaroo Mother Care (KMC) method. This study aims to determine changes in the anxiety levels of postpartum mothers after receiving KMC intervention. The study used a one-group pretest-posttest design with 16 respondents selected through incidental sampling. Data was collected using the Perinatal Anxiety Screening Scale (PASS) questionnaire. After the KMC intervention, there was a change in the anxiety levels of the respondents, with seven respondents (43.8%) experiencing mild anxiety and eight respondents (56.3%) experiencing moderate anxiety. Statistical analysis using a paired t-test showed a p-value of 0.000 (p < 0.05), indicating a significant difference between pre- and post-intervention levels. Before the intervention, anxiety levels among respondents were predominantly in the moderate to severe category. After the KMC intervention, anxiety levels decreased to the moderate to mild category. This indicates that the KMC intervention has a positive effect in reducing anxiety levels among postpartum mothers at RSU Pancaran Kasih Manado.